Behavioural finance: The~decoy~effect on stock investment decisions - Bruno Uekane Okumura; Tabajara Pimenta Júnior; Márcia Mitie Durante Maemura; Luiz Eduardo Gaio; Rafael Confetti Gatsios (Journal of Economics, Finance and Administrative Science, 2023)
Purpose - This study aims to investigate the occurrence of the decoy effect in stock investment decisions based on fundamental analysis. Design/methodology/approach In this study, the decoy effect was investigated by applying two questionnaires, one of them with the presence of a decoy alternative, to a set of 224 respondents with knowledge of business fundamentals, simulating investment decisions in stocks of companies listed on the Brazilian Stock Exchange. The data analysis was performed using the Fisher's exact test, Student's t-test and ANOVA. The research also aimed to detect a potential relationship between the variables gender, age, degree and professional experience with the type of decision made. Findings The results pointed to the occurrence of the decoy effect when analysing the general response data. However, such evidence was not confirmed when the sample was analysed by classes (gender, course, age and professional experience). There is no statistical evidence that the decoy effect influences classes. Originality/value The recent decoy effect literature is little explored in investment decision-making. This study is unique in examining the decoy effect in investment decisions in the Brazilian context.
Keywords: D91; G11; G41; 330; Behavioural finance; Decoy effect; Investment decisions